2018
DOI: 10.1002/cncr.31581
|View full text |Cite
|
Sign up to set email alerts
|

The added value of geriatric screening and assessment for predicting overall survival in older patients with cancer

Abstract: BACKGROUND:The aim of this study was to determine and compare the added prognostic value of screening tools, geriatric assessment (GA) components, and GA summaries to clinical information for overall survival (OS) in older patients with cancer. METHODS: A screening and a 10-item GA were systematically performed in patients ≥70 years old with cancer. Cox regression analyses were conducted to evaluate the added prognostic value for OS of screening tools, GA, and GA summaries to clinical information (age, stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…4 This study has been reported extensively previously. 4 This study has been reported extensively previously.…”
Section: Designmentioning
confidence: 82%
See 4 more Smart Citations
“…4 This study has been reported extensively previously. 4 This study has been reported extensively previously.…”
Section: Designmentioning
confidence: 82%
“…27 When taken together, this 10-item GA is a GA summary that integrates the results of every GA component mentioned above and thus captures the multidimensional GA as a whole evaluating the global health of the older patient with cancer. 4 Therefore, in the current study, we primarily compared the added prognostic value of the 10-item GA with that of laboratory parameters. In our previous article, we demonstrated that the 10-item GA provides more prognostic information than the individual GA components and screening tools because GA summaries are likely better at capturing the multidimensional process of aging.…”
Section: Geriatric Assessmentmentioning
confidence: 99%
See 3 more Smart Citations